La enseñanza de la Matemática mediante la resolución de problemas, para lograr un aprendizaje significativo en los estudiantes del décimo año de Educación General Básica en la Unidad Educativa San José de Guaytacama. - Ortega Proaño, Pablo David (2020)
The present research work addresses a problem related to the teaching of Mathematics in the tenth year of GBE, where the general objective was to develop a didactic or methodological alternative to improve the teaching of Mathematics and therefore learning in the tenth year of General Basic Education. In order to achieve the objective, the following methodology was used: theoretical, empirical and statistical methods. In addition, some techniques such as the checklist and the questionnaire were used, obtaining as a result the proposal to strengthen the teaching of Mathematics through problem solving, in order to achieve a significant learning in the students, which was validated through user criteria, arriving at the following conclusion: through the application of the problem solving technique, a significant improvement in the teaching of Mathematics was achieved.